The Persistence of Yōkai - Zack Davisson (Education About Asia, 2026)
This article examines the evolution and cultural persistence of yōkai—Japanese supernatural entities—across Japanese history, with particular focus on their transformation through key cultural periods and the role of influential creators. It demonstrates how individual creators served as cultural mediators, actively shaping and preserving yōkai traditions while adapting them to contemporary media formats, and how traditional yōkai narratives maintain cultural relevance through continuous reinterpretation and adaptation to new storytelling media. This resource contributes to our understanding of how traditional folklore elements survive and evolve through deliberate creative intervention, ensuring their continued resonance with contemporary audiences both within Japan and globally.
Keywords: Japan; Yokai; folklore; storytelling; monsters